Trudne dziedzictwo: Problem cmentarzy ukraińskich na terenach postmigracyjnych Polski Południowo-Wschodniej .......... 133 - Kich-Masłej, Olga (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
DIFFICULT HERITAGE: THE PROBLEM OF UKRAINIAN CEMETERIES IN THE POST-IMMIGRATION AREAS OF SOUTH-EASTERN POLANDUkrainian cemeteries in the post-immigration areas of south-eastern Poland have never been fully documented and developed. Considering that there may be over several hundred such cemeteries in Poland, this situation is difficult to accept. Due to the complicated legal status and numerous instances of failure to respect sacredness of cemeteries, in November 2018 the case was dealt with by the Polish Ombudsman for Citizen Rights Adam Bodnar. Detailed inventories of all cemeteries in the territory of present-day Poland are necessary to be made. The uncomfortable question of the causes of destruction must also be posed.